HIV Nef-mediated Ubiquitination of BCL2: Implications in Autophagy and Apoptosis - Castro-Gonzalez, Sergio; Simpson, Sydney; Shi, Yuhang; Chen, Yuexuan; Benjamin, Jared; Serra-Moreno, Ruth (Frontiers in Immunology, 2021)
Ubiquitination is a process that acts upon every step of the HIV replication cycle. The activity, subcellular localization, and stability of HIV dependency factors as well as negative modulators can be affected by ubiquitination. These modifications consequently have an impact on the progression and outcome of infection. Additionally, recent findings suggest new roles for ubiquitination in the interplay between HIV and the cellular environment, specifically in the interactions between HIV, autophagy and apoptosis. On one hand, autophagy is a defense mechanism against HIV that promotes the degradation of the viral protein Gag, likely through ubiquitination. Gag is an essential structural protein that drives virion assembly and release. Interestingly, the ubiquitination of Gag is vital for HIV replication. Hence, this post-translational modification in Gag represents a double-edged sword: necessary for virion biogenesis, but potentially detrimental under conditions of autophagy activation. On the other hand, HIV uses Nef to circumvent autophagy-mediated restriction by promoting the ubiquitination of the autophagy inhibitor BCL2 through Parkin/PRKN. Although the Nef-promoted ubiquitination of BCL2 occurs in both the endoplasmic reticulum (ER) and mitochondria, only ER-associated ubiquitinated BCL2 arrests the progression of autophagy. Importantly, both mitochondrial BCL2 and PRKN are tightly connected to mitochondrial function and apoptosis. Hence, by enhancing the PRKN-mediated ubiquitination of BCL2 at the mitochondria, HIV might promote apoptosis. Moreover, this effect of Nef might account for HIV-associated disorders. In this article, we outline our current knowledge and provide perspectives of how ubiquitination impacts the molecular interactions between HIV, autophagy and apoptosis